Knowledge Sharing In The Jordanian Universities - Alhammad, Fawwaz; Al Faori, Sameera; Husan, Lama Suleiman Abu (Journal of Knowledge Management Practice, 2009)
This study investigates knowledge sharing in the Jordanian universities by analyzing the relationships between staff's attitudes toward knowledge sharing and their demographic variables. After interviewing 300 participants; it has been found that the academic staff are less interested in sharing their knowledge than administrative staff. The study provides solutions for the practitioners and recommendations for the researchers in this field.
Keywords: Knowledge management; Knowledge sharing; Education; Middle East; Jordan